Transforming the interrelated nature of human psychoneuroendocrine health and endocrine disrupting compounds in our planet’s water: from Wilhelm Waldeyer’s neuron theory to an artificial intelligence extension of the human body? - Schweizer-Schubert, Sophie; von Waldeyer-Hartz, Götz; Schütze, Susann-Elisabeth; Mahringer, Daniel; Ruhl, Aki Sebastian; Graf, Markus; Kuckelkorn, Jochen (Frontiers in medicine, 2025)
The interplay between steroid hormones (reproductive and stress hormones) and mental and physical health has evolved as an important area of medical and psychological research. At the same time, endocrine disrupting compounds (EDCs) spreading via our planet’s water have become a focus in environment- and health-related sciences, as well as in the public interest. The impact of EDCs on the delicate hormonal balance essential to human health remains insufficiently understood. The Federal Ministry of Health in Germany deemed this topic so important that it tasked the German Environment Agency with conducting a nationwide, effect-directed analysis of EDCs in drinking water. Our interdisciplinary research collaboration, providing its scientific foundation, includes expertise from medicine, psychology, biology, ecotoxicology, technology, and artificial intelligence. The objective of this review is the assessment of endocrine effects caused by drinking water on the human body and the reduction of EDCs in the urban water cycle emitted by the human body. Our specific goals are to gain a better understanding of human psychoneuroendocrine health in relation to the EDC problem, to identify gaps in current research and to explore measures for reducing the human body’s emissions of EDCs. This assessment is particularly relevant given the anticipated global rise in the use of contraceptives, infertility treatments, hormone-replacement therapies and endocrinological treatments of stress-related disorders, all of which contribute to increased endocrine-disrupting compounds in the water cycle. Leveraging artificial intelligence and virtual human twin technologies to simulate individualized hormonal responses provide valuable insights into possible targeted interventions for reducing EDCs by personalized endocrinological practice.
Online veröffentlicht am 15. September 2025
Gesehen am 10.02.2026